Inflammation Fueling Atrial Fibrillation Substrate: Seeking Ways to “Cool” the Heart - Giannopoulos, Georgios; W. Cleman, Michael; Deftereos, Spyridon (Medicinal Chemistry, 2014)
Atrial fibrillation (AF) is the most common chronic arrhythmia and a source of significant morbidity and mortality. Previous studies have identified numerous risk factors for the development of AF, including hypertension, diabetes mellitus and heart failure, which have known pathophysiologic links with inflammatory processes. The importance of inflammation in inducing and perpetuating AF has been highlighted not only by experimental, epidemiological and cohort observational studies, but also by clinical trials providing evidence that inflammatory pathways are involved in AF pathogenesis. Local and systemic measurements of biomarkers and inflammatory mediators, as well as atrial biopsy studies have also given insight as to the purported relationship between this arrhythmia and inflammation. However, the link between inflammation and AF is still poorly defined and several issues remain unresolved. The present review offers an overview of existing evidence supporting the “inflammatory” hypothesis for AF pathophysiology and potential therapeutic means for counteracting this “foul interplay” between arrhythmia and inflammation.
Keywords: atrial fibrillation